Penyuluhan Penyusunan Anggaran Fleksibel bagi Karyawan Perusahaan Bagian Akuntansi di Jakarta - Nelli Novyarni; Reni Harni; Kartijo Kartijo; Ira Maysa A (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
A training program on flexible budgeting has been conducted involving 35 accounting employees from various companies in Jakarta, aiming to enhance participants' capacity in understanding and implementing flexible budgeting concepts in their daily work practices, considering that flexible budgeting plays a strategic role in corporate financial management as it enables adjustment of projections and fund allocations according to changes in activity volume and evolving business environment dynamics. The program employed a participatory approach through material delivery, interactive discussions, and real-case simulations, where participants were equipped with knowledge regarding budgeting preparation stages, fixed and variable cost analysis techniques, and the application of flexible budgeting as a managerial decision-making instrument, with evaluation conducted using pre-tests and post-tests to measure understanding levels before and after the program. Evaluation results indicated a significant improvement in participants' understanding of flexible budgeting concepts and techniques that are more adaptive and efficient, thus the program is expected to provide long-term impacts in the form of enhanced professional competency of accounting employees and encourage companies to develop budgeting systems that are more responsive to business condition fluctuations and market changes.